(untitled) (Research, Society and Development, 2021)
It is of fundamental importance to make the population aware of the use of water resources, increasingly exposing society that they depend on a period of regeneration and that irresponsible use causes water shortages. The objective is to evaluate and compare the performance of empirical methods for estimating evapotranspiration by the methods of Hargreaves, Hargreaves-Samani, Camargo and Thorntwaite with the standard method of Penman-Monteih, suggested by FAO-56, for Amparo de São Francisco – Sergipe. The rainfall data were from the period 1963-2020 and the thermal data were estimated by the software estima - T. The climatological data were estimated by the simplified interpolation method. With the results, it became clear that land use changes, such as agriculture, grazing and reforestation, cause changes in the water dynamics of a watershed. The Penman - Monteith method indicated by the FAO for the determination of ETp, present values ​​different from the real water conditions, at least in the studied area, overestimating the monthly ETp in all studied land uses. This behavior may be linked to solar radiation and temperature, which are the determining factors for the estimation of evapotranspiration by the Penman-Monteith method.